User-centered design and evaluation of e-heritage: a virtual reality prototype for learning architectural heritage in informal education - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen; Mahmud, Murni; Buyong, Kamarul Bahrin; Ali, Maisarah (CONVR2010 Organizing Committee, 2010)
The importance of user-centered design and evaluation of virtual reality application (VR) cannot be underestimated, especially for the development of applications that involves massive users. Based on an ongoing effort to develop a usable and meaningful VR to learn cultural heritage through architectural monuments, a series of user evaluation is required to identify usability issues and design improvements from user perspective.Museums has been selected as representatives of informal education settings, based on their role in the dissemination and popularization of knowledge of cultural heritage to the general public and the acquisition and preservation of heritage to displayed and disseminated among public. The objective of this paper is to deliver the results of such evaluation through gauging and analyzing the feedback and subjective opinions of the actual users of the system. This is to subsequently allow for a better implementation of modifications aimed at improving fidelity of the user interface and ease of the system in informal education. Progression and performance is evaluated as this is determined by user's ability to navigate in the VR environment and then recall historical as well as architectural information in order to impart architectural knowledge to the users. Result will provide a systematic approach of the evaluation of the VR system, information for guidance on system refinements and hence allow for comparison of usability levels with other types of learning systems.